Communication Management Strategy in the Development of Culinary Tourism Destinations in Serang City - Asih Kurnianingsih; Rina Fitriana; Nina Yuliana; Husnan Nurjuman; Muhammad Jaiz (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
The development of culinary tourism in urban areas is increasingly viewed as a regional development strategy that not only boosts the local economy but also strengthens urban spatial planning and destination image. This study aims to analyze communication management strategies in the development of two culinary tourism destinations in Serang City, namely Pasar Lama Culinary Tourism and Kepandean Culinary Tourism, specifically in the process of vendor relocation, stakeholder coordination, and destination promotion. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive analysis model. The results show that the Serang City Government's communication strategy is implemented through policy communication to build relocation legitimacy, coordinative communication to strengthen collaboration between actors, and promotional communication through social media and events. However, the implementation of these strategies has not been fully optimal due to inconsistent promotional messages, weak destination branding management, and limited integration of cross-stakeholder communication. This study concludes that the successful development of culinary tourism based on urban planning requires planned, integrated, and consistent communication management to shape the destination image and increase regional competitiveness. The contribution of this research lies in strengthening the perspective of communication management in the development of urban culinary tourism, especially in the context of new destinations born from relocation policies and revitalization of regional assets.